Peningkatan Hasil Belajar Siswa Kelas IV pada Pembelajaran IPA dengan Model Pembelajaran Make A Match Di SDN 12 Api-Api Pesisir Selatan - Donni Saputra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
The purpose of this study was to describe the improvement of student learning outcomes IPA with Model make a match at SDN 12 Api-Api. This type of research is the Classroom Action Research (PTK) is conducted in two cycles. The data source is the fourth grade students of SDN 12 Api-Api numbered 17 people. The instrument used in this study is the assessment sheet affective student, teacher activity sheet and test the students' understanding. Based on analysis of the affective ratings of students In the first cycle the change in student behavior responsibilities increased 51.0% to 83.3% in the second cycle and the change in behavior of the cooperation of students in the first cycle of 44.1% increased to 74.5% in the second cycle. The results of cognitive learning that an understanding had also increased. In the first cycle student comprehension 58.8% increase to 82.4 in the second cycle. From the data obtained it can be concluded that there is a learning outcome IPA fourth grade students of SDN 12 Api-Api after using the model make a match.